Cardiac‐Specific Disruption of Bin1 in Mice Enables a Model of Stress‐ and Age‐Associated Dilated Cardiomyopathy. Issue 11 (9th September 2015) - Laury‐Kleintop, Lisa D.; Mulgrew, Jennifer R.; Heletz, Ido; Nedelcoviciu, Radu Alexandru; Chang, Mee Young; Harris, David M.; Koch, Walter J.; Schneider, Michael D.; Muller, Alexander J.; Prendergast, George C.
ABSTRACT Non‐compensated dilated cardiomyopathy (DCM) leading to death from heart failure is rising rapidly in developed countries due to aging demographics, and there is a need for informative preclinical models to guide the development of effective therapeutic strategies to prevent or delay disease onset. In this study, we describe a novel model of heart failure based on cardiac‐specific deletion of the prototypical mammalian BAR adapter‐encoding gene Bin1, a modifier of age‐associated disease. Bin1 deletion during embryonic development causes hypertrophic cardiomyopathy and neonatal lethality, but there is little information on how Bin1 affects cardiac function in adult animals. Here we report that cardiomyocyte‐specific loss of Bin1 causes age‐associated dilated cardiomyopathy (DCM) beginning by 8–10 months of age. Echocardiographic analysis showed that Bin1 loss caused a 45% reduction in ejection fraction during aging. Younger animals rapidly developed DCM if cardiac pressure overload was created by transverse aortic constriction. Heterozygotes exhibited an intermediate phenotype indicating Bin1 is haplo‐insufficient to sustain normal heart function. Bin1 loss increased left ventricle (LV) volume and diameter during aging, but it did not alter LV volume or diameter in hearts from heterozygous mice nor did it affect LV mass. Bin1 loss increased interstitial fibrosis and mislocalization of the voltage‐dependent calcium channel Cav1.2, and the lipid raft scaffold protein caveolin‐3, which normally complexes with Bin1 and Cav1.2 in cardiomyocyte membranes. Our findings show how cardiac deficiency in Bin1 function causes age‐ and stress‐associated heart failure, and they establish a new preclinical model of this terminal cardiac disease. J. Cell. Biochem. 116: 2541–2551, 2015. © 2015 Wiley Periodicals, Inc.